2018
DOI: 10.1002/johc.12080
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Complex Trauma: An Existential View of Adverse Childhood Experiences

Abstract: Adverse childhood experiences (ACEs) can trigger a variety of existential reactions that disrupt physical, mental, and behavioral health. This article explores the implications of ACEs for the development of children, adolescents, and adults. Examining ACEs through an existential lens, the authors provide a way to conceptualize clients with multiple ACEs and offer suggestions for interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…The results of this investigation revealed that very few articles published in ACA-and ASCA-affiliated journals in the 20 years since Felitti et al's (1998) study explicitly named ACEs in the title, abstract, or keywords. Of the three articles published mentioning ACEs in the title, abstract, or keywords between 1998 and 2018, two were conceptual articles (Navalta et al, 2018;Zyromski et al, 2018), whereas the third (Rausch, 2016) was a quantitative analysis of the relationship between ACEs and intimate partner violence in adult samesex, female-committed, monogamous relationships. Rausch (2016) demonstrated an additional predictive link between ACEs and negative outcomes related to the development of healthy relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this investigation revealed that very few articles published in ACA-and ASCA-affiliated journals in the 20 years since Felitti et al's (1998) study explicitly named ACEs in the title, abstract, or keywords. Of the three articles published mentioning ACEs in the title, abstract, or keywords between 1998 and 2018, two were conceptual articles (Navalta et al, 2018;Zyromski et al, 2018), whereas the third (Rausch, 2016) was a quantitative analysis of the relationship between ACEs and intimate partner violence in adult samesex, female-committed, monogamous relationships. Rausch (2016) demonstrated an additional predictive link between ACEs and negative outcomes related to the development of healthy relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Navalta et al (2018) suggested a neurocounseling approach, encouraging counselors to use ACEs and the neurobiology of the brain starting with case conceptualization and continuing with the integration of evidence-based treatments. Zyromski et al (2018) endorsed viewing ACEs from an existential counseling lens, proposing that counselors might better understand ACEs through clients' lived experiences and promote wellness using existential therapeutic interventions (e.g., emotion regulation, sense of self).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term trauma can describe many types of experiences, including experiencing interpersonal violence; witnessing violence against a loved one; and experiencing the effects of war, natural disaster, or ongoing toxic stress (Bucci, Marques, Oh, & Burke Harris, 2016; Coursol, Lewis, & Garrity, 2001). When individuals experience trauma early in life, it can negatively affect their physical, mental, and behavioral health across the life span (Anda et al, 2006; Centers for Disease Control and Prevention [CDC], 2018; Zyromski et al, 2018). Ten specific types of childhood trauma were measured in the original ACE study (Bucci et al, 2016; Felitti et al, 1998).…”
Section: Ace Studymentioning
confidence: 99%
“…Yet, the counseling literature remains in the early process of integrating these critical findings. Zyromski et al (2018) found that in 21 journals published by the American Counseling Association and its member divisions, only one article referred to the topic of ACEs (i.e., Rausch, 2016). The ACE study is changing practice across many disciplines in the helping professions, and counseling professionals could also use this information to examine counseling practices in light of the implications of ACEs, toxic stress, and trauma‐informed practices.…”
mentioning
confidence: 99%